Policy and education - Adams, Paul (Routledge, 2014)
"Written specifically for education studies students, this accessible text offers a clear introduction to education policy. It aims to help the reader understand what is meant by educational policy, how policy can be made and the main discourses that have driven education. Capturing the essential aspects of educational policy over the last thirty years, the book provides an overview of political themes in education demonstrating how education policy has progressed and the effect this and politics have had on schools. It then covers key themes such as performance, choice and professionalism to show how education policy is constructed and implemented and how this has impacted on education in practice. Features include: - activities that can be undertaken individually or as a group to promote discussion - annotated further reading lists; - chapter overviews and summaries Written as part of the Foundations in Education Studies series, this timely textbook is essential reading for students coming to the study of education policy for the first time"--